Securitization of the new media : are states successful in resisting a rising tide? - Shiran Ali Kassim Ali. (2010)
New media today, spurred by the advent of the latest Information and Communications Technologies (ICTs) has given rise to a myriad of ways in which human communication has evolved. Technologies, such as the Internet, have shaped not just the way in which people communicate, but have also shaped our understanding of communications phenomenon, unveiling the vulnerable underbellies of states to other states as well as non-state actors. As states become more aware of the threat possibilities in which new media poses, securitization of the new media, albeit in some cases significant aspects of it, becomes an increasingly prevalent practice.